(untitled) (Journal of Basic and Applied Research in Biomedicine, 2023)
Breast cancer presents varied and complex clinicopathological features which make its management individualistic, prolonged and expensive, thus the need to differentiate each type of breast cancer using cheap and easy to perform investigations. This study evaluated the differentiation potential of extensive immune-nutritional indices which combined serum C-reactive protein (CRP), haemoglobin, albumin levels, blood lymphocyte and platelet counts in breast cancer patients of different status. The aim of this study was to investigate whether pre-treatment Onodera’s prognostic nutritional index (OPNI), CRP-Albumin-Lymphocyte (CALLY) index and the Haemoglobin, Albumin, Lymphocyte and Platelet (HALP) scores differ with breast cancer characteristics. We enrolled a total of 135 consecutive newly diagnosed breast cancer patients who were not on any treatment from Radiation Oncology Department, University College Hospital, Ibadan, Nigeria. Lymphocyte count, platelet count and haemoglobin levels were determined using auto-analyser while serum CRP and albumin levels were measured using ELISA. Immune-nutritional indices (OPNI, CALLY and HALP) were calculated. Haemoglobin concentration, serum albumin level, OPNI, CALLY and HALP were significantly decreased while serum CRP was significantly raised in breast cancer patients compared with control. Mean values of OPNI, CALLY and HALP were significantly decreased in late stage breast cancer patients compared with early stage breast cancer patients, while only CALLY was significantly decreased in poorly differentiated and metastatic breast cancer patients compared with well differentiated and non-metastatic breast cancer patients respectively. This study confirmed the presence of malnutrition and inflammation in breast cancer patients, especially late-stage, poorly differentiated and metastatic groups. This calls for monitoring of liver functions in all cases of breast cancer.